A New Strategy for Antidepressant Prescription - Lavergne, Francis; Jay, Therese M. (Frontiers in Neuroscience, 2010)
From our research and literature search we propose an understanding of the mechanism of action of antidepressants treatments (ADTs) that should lead to increase efficacy and tolerance. We understand that ADTs promote synaptic plasticity and neurogenesis. This promotion is linked with stimulation of dopaminergic receptors. Previous evidence shows that all ADTs (chemical, electroconvulsive therapy, repetitive transcranial magnetic stimulation, sleep deprivation) increase at least one monoamine neurotransmitter serotonin (5-HT), noradrenaline (NA) or dopamine (DA); this article focuses on DA release or turn-over in the frontal cortex. DA increased dopaminergic activation promotes synaptic plasticity with an inverted U shape dose–response curve. Specific interaction between DA and glutamate is mediated by D1 receptor subtypes and Glutamate (NMDA) receptors with neurotrophic factors likely to play a modulatory role. With the understanding that all ADTs have a common, final, DA-ergic stimulation that promotes synaptic plasticity we can predict that (1) AD efficiency is related to the compound strength for inducing DA-ergic stimulation. (2) ADT efficiency presents a therapeutic window that coincides with the inverted U shape DA response curve. (3) ADT delay of action is related to a “synaptogenesis and neurogenesis delay of action.” (4) The minimum efficient dose can be found by starting at a low dosage and increasing up to the patient response. (5) An increased tolerance requires a concomitant prescription of a few ADTs, with different or opposite adverse effects, at a very low dose. (6) ADTs could improve all diseases with cognitive impairments and synaptic depression by increasing synaptic plasticity and neurogenesis.